This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Using the chebyshev polynomial T 7 = 6 4 x 7 − 1 1 2 x 5 + 5 6 x 3 − 7 x , the roots to T 7 ( x ) = 1 are cos 7 2 n π .
Lets factor out ( x − 1 ) from T 7 ( x ) − 1 : T 7 ( x ) − 1 = ( x − 1 ) ( 6 4 x 6 + 6 4 x 5 − 4 8 x 4 − 4 8 x 3 + 8 x 2 + 8 x + 1 ) .
The zeroes of the second factor are cos 7 2 π , cos 7 4 π , cos 7 6 π , cos 7 8 π , cos 7 1 0 π , cos 7 1 2 π .
Taking the mapping x → x 1 , the factor becomes x 6 + 8 x 5 + 8 x 4 − 4 8 x 3 − 4 8 x 2 + 6 4 x + 6 4 . The zeroes of this are sec 7 2 π , sec 7 4 π , sec 7 6 π , sec 7 8 π , sec 7 1 0 π , sec 7 1 2 π .
Finally, we apply newton's identities and want to calculate P 4 .
P 1 = − 8
P 2 = ( − 8 ) P 1 − 8 × 2 = 4 8
P 3 = ( − 8 ) P 2 − 8 P 1 + 4 8 × 3 = − 1 7 6
P 4 = ( − 8 ) P 3 − 8 P 2 + 4 8 P 1 − ( − 4 8 ) × 4 = 8 3 2
Now, since sec 7 π = − sec 7 8 π = − sec 7 6 p i ,
and sec 7 2 π = sec 7 1 2 π ,
and sec 7 3 π = − sec 7 4 π = − sec 7 1 0 p i ,
Hence we conclude that
sec 4 7 2 π + sec 4 7 4 π + sec 4 7 6 π + sec 4 7 8 π + sec 7 1 0 π 4 + sec 4 7 1 2 π = 2 ( sec 4 7 π + sec 4 7 2 π + sec 4 7 3 π )
Hence, the expression is 2 8 3 2 = 4 1 6 .
Note: The solution could be simplified by making the observation about the duplicity of roots first. If so, we can conclude that the polynomial whose roots are cos 7 π , cos 7 2 π , cos 7 3 π is given by x − 1 T 7 ( x ) − 1 = 8 x 3 − 4 x 2 − 4 x + 1 , and then using x → x 1 and newton identities accordingly. Give it a try!